A common control channel selection algorithm for cognitive wireless mesh networks. (2015) - Liu, Chunxiao; Sun, Dawei; Li, Shifeng; Xu, E.
Aiming to solve the problem of the common control channel selection algorithm for cognitive wireless mesh networks, a novel common control channel selection algorithm is proposed in this paper. As different cognitive users may have different channels in the available channel list, multiple channels will be selected as the common control channel in the algorithm proposed in this paper. In order to reduce the delay generated by channel switching, both the probability that a channel may be selected as the common control channel and the time that primary users have occupied the channel in the last cycle will be considered in this paper. At last, simulation results show that the number of common control channels in the network can be controlled effectively, the time of network establishment will be reduced and the average communication successful rate will be improved.